Rubber flip-flop wheels to the fight - Abreu e Souza, Rafael de (2021)
This paper investigates the material culture from Brazilian semiarid hinterland peasants focusing on wheels made of rubber flip-flops as creative materialities that invert the presumed functions of industrialized products within the scope of peasant logics. The approach is archaeological, diachronic and regional to analyse discarded things found in peasant households from Ceará, Piauí and Pernambuco states. It is critical to discourses of poverty, isolation, cultural homogeneity and death of the peasantry in face of the arrival of urban industrial consumerist and modern logics to those hinterlands. The wheels, representing the children's universe, allow us to notice how symbolic economies appropriate modern objects creating new materialities from their reuse.